Breast Pain in a Lactating Person: An Objective Structured Clinical Examination for Clerkship Students - Nicola Young; Kelly Branford; Deborah L. Engle; Sarah K. Dotters-Katz; Andrea Dotson (MedEdPORTAL)
Introduction Breastfeeding provides significant health benefits for families and cost-saving potential for health care systems. Physician support is crucial to lactation success. However, lactation education curricula across the US do not reliably meet published standards, and educators lack a standardized tool to assess student competency. We developed a breastfeeding-focused OSCE for UME learners that assesses students’ application of lactation knowledge in clinical settings. Methods This lactation OSCE for medical students includes a patient interview, postencounter note, and evaluation by a trained standardized patient (SP). OSCE performance was compared between clerkship students who participated in a pilot lactation curriculum and students who did not participate in this curriculum. Primary outcome was correct identification of primary diagnosis. Secondary outcomes included postencounter note total score, history score, management/counseling score, and SP communication score. Data were analyzed using bivariate statistics. Results Twenty-eight students completed the OSCE, of whom 15 (54%) participated in the pilot lactation curriculum. Pilot students were more likely than nonpilot students to correctly identify the primary diagnosis (73% vs. 31%, p = .02), score higher on management/counseling (median 4.0 [IQR: 4.0, 6.0] vs. 4.0 [IQR: 2.0, 4.0], p = .04), and communicate better (73% vs. 63%, p = .002), and also nearly twice as likely to score ≥50th percentile overall (73% vs. 39%, p = .06) and have higher total postencounter note scores (median 22.0 [IQR: 20.0, 26.0] vs. 19.0 [IQR: 18.0, 22.0], p = .18). Discussion This OSCE effectively assesses UME learners’ ability to clinically apply lactation knowledge.